Rheumatoid Arthritis and Incidence of Twelve Initial Presentations of Cardiovascular Disease: A Population Record-Linkage Cohort Study in England. - Mar Pujades-Rodriguez; Bram Duyx; Sara L Thomas; Dimitris Stogiannis; Anisur Rahman; Liam Smeeth; Harry Hemingway (PLoS ONE)
Introduction While rheumatoid arthritis is an established risk factor for cardiovascular disease (CVD), our knowledge of how the pattern of risk varies for different cardiovascular phenotypes is incomplete. The association between rheumatoid arthritis and the initial presentation of 12 types of CVDs were examined in a contemporary population of men and women of a wide age range. Methods CALIBER data, which links primary care, hospital and mortality data in England, was analysed. A cohort of people aged ≥18 years and without history of CVD was assembled and included all patients with prospectively recorded rheumatoid arthritis from January 1997, until March 2010, matched with up to ten people without rheumatoid arthritis by age, sex and general practice. The associations between rheumatoid arthritis and the initial presentation of 12 types of CVDs were estimated using multivariable random effects Poisson regression models. Results The analysis included 12,120 individuals with rheumatoid arthritis and 121,191 comparators. Of these, 2,525 patients with and 18,146 without rheumatoid arthritis developed CVDs during a median of 4.2 years of follow-up. Patients with rheumatoid arthritis had higher rates of myocardial infarction (adjusted incidence ratio [IRR] = 1.43, 95%CI 1.21-1.70), unheralded coronary death (IRR = 1.60, 95%CI 1.18-2.18), heart failure (IRR = 1.61, 95%CI 1.43-1.83), cardiac arrest (HR = 2.26, 95%CI 1.69-3.02) and peripheral arterial disease (HR = 1.36, 95%CI 1.14-1.62); and lower rates of stable angina (HR = 0.83, 95%CI 0.73-0.95). There was no evidence of association with cerebrovascular diseases, abdominal aortic aneurysm or unstable angina, or of interactions with sex or age. Conclusions The observed associations with some but not all types of CVDs inform both clinical practice and the selection of cardiovascular endpoints for trials and for the development of prognostic models for patients with rheumatoid arthritis.